Autonomisation des femmes dans l’utilisation des SIC - Govoeyi, Benoit; Diedhiou, Lamine; Ka, Binetou; Worou, Nadine (International Livestock Research Institute, 2025)
This report summarizes the outcomes of a training of trainers held from 16 to 18 September 2025 in Thiès, Senegal, under the AICCRA project in collaboration with RESOPP. The training aimed to strengthen the capacities of agricultural and pastoral producer organizations to promote women’s empowerment in accessing and using Climate Information Services (CIS). Facilitated by ILRI’s Gender and Social Inclusion Expert, the sessions combined lectures, group discussions, and pre- and post-training evaluations. The modules covered gender and climate change, climate justice, inclusive governance of CIS, and approaches to enhance women’s participation in decision-making related to climate adaptation. Test results revealed a significant improvement in participants’ understanding, with incorrect responses decreasing from 52–71% before training to 20–30% afterward. The workshop equipped trainers with the tools to cascade knowledge to rural communities, supported by AICCRA and RESOPP experts. The experience demonstrates the effectiveness of participatory and gender-sensitive approaches in strengthening climate resilience within Senegal’s agricultural systems and highlights the importance of continued training and support for rural women in the use of climate information services.